The Quality of Parliamentary Deliberation: The Case of the Family Code Debates in the Slovenian Parliament - Kuhar, Metka; Petrovčič, Andraž (Javnost-The Public, 2017)
Researching the case of the transnational European conflict around the Greek and Euro crisis, this article explores whether and to what extent the media representations of the very early stages of the crisis in 2009/10 in the German and Spanish quality press feature “national orientations” or indicate a Europeanised, common European debate. Based on a content analysis of the news coverage of German and Spanish quality newspapers, the analysis reveals a multidimensional picture of the news coverage; it is Europeanised and shaped by national orientations at the same time. The transnational politicisation of European politics fosters the simultaneous visibility of issues of common concern across national borders. Furthermore, Europe or the European Union as a collective body and reference object for identification is highly visible. But transnational integrated speaker ensembles and a common European debate remain demanding. The media in Germany and Spain still feature national orientations with respect to the speakers cited in the news and with respect to the frames and viewpoints on the crisis phenomena.